Course of psychotic experiences and disorders among apprentice traditional health practitioners in rural South Africa: 3-year follow-up study - van der Zeijst, Martine C. E.; Veling, Wim; Makhathini, Elliot M.; Mbatha, Ndukuzakhe D.; Shabalala, Sinethemba S.; van Hoeken, Daphne; Susser, Ezra; Burns, Jonathan K.; Hoek, Hans W. (Frontiers in Psychiatry, 2022)
Background Culture is inevitably linked with the experience, interpretation and course of what modern biomedicine understands to be psychotic symptoms. However, data on psychoses in low- and middle-income countries are sparse. Our previous study showed that psychotic and mood-related experiences, symptoms and disorders are common among individuals who had received the ancestral calling to become a traditional health practitioner (THP) in rural KwaZulu-Natal, South Africa. Our related ethnographic study suggested that ukuthwasa (the training to become a THP) may positively moderate these calling-related symptoms. As far as we know, no research has been conducted into the course of psychiatric symptoms among apprentice THPs. Objective We studied the course of psychotic experiences, symptoms and disorders among apprentice THPs. We also assessed their level of functioning and expanded our knowledge on ukuthwasa. Materials and methods We performed a 3-year follow-up of a baseline sample of apprentice THPs (n = 48). Psychiatric assessments (CAPE, SCAN), assessment of functioning (WHODAS) and a semi-structured qualitative questionnaire were completed for 42 individuals. Results At 3-year follow-up, psychotic experiences were associated with significantly less distress and there was a reduction in frequency of psychotic symptoms compared to baseline. The number of participants with psychotic disorders had decreased from 7 (17%) to 4 (10%). Six out of seven participants (86%) with a psychotic disorder at baseline no longer had a psychiatric diagnosis at follow-up. Although the mean level of disability among the (apprentice) THPs corresponded with the 78th percentile found in the general population, 37 participants (88%) reported no or mild disability. Forty-one participants (98%) reported that ukuthwasa had positively influenced their psychiatric symptoms. Conclusion In rural KwaZulu-Natal, psychotic experiences, symptoms and disorders have a benign course in most individuals who are undergoing the process of becoming a THP. Ukuthwasa may be an effective, culturally sanctioned, healing intervention for some selected individuals, potentially because it reframes distressing experiences into positive and highly valued experiences, reduces stigma, and enhances social empowerment and identity construction. This implies that cultural and spiritual interventions can have a positive influence on the course of psychosis.